Mediation Regulation Re-Arrangement’s Efforts At The State Court Based On Confidential Principles As The Parties’ Protection - Rika Destiny Sinaga; Joni Emirzon; Muhammad Syaifuddin (Universitas Lampung, 2022)
Mediation has a confidentiality principle as an advantage that should be able to safeguard the reputation of the disputing parties. Still, mediation arrangements in district courts are influenced by the principle of open trial to the public, causing problems, which are; how is the confidentiality principle-based mediation arrangement in district courts in providing protection for the reputation of the party in the dispute and how efforts to reform mediation arrangements in court to realize the confidentiality principle in settlement of civil cases in district courts which is oriented towards legal protection of the reputation of the litigant by using normative legal research that uses primary, secondary and tertiary legal materials collected by document study and then analyzed using descriptive, comparative, evaluative and argumentative techniques. The conclusion is that the mediation procedure in court is regulated by the Supreme Court Regulation Number 02 of 2003 then replaced by the Supreme Court Regulation Number 01 of 2008. Finally, the Supreme Court Regulation Number 1 of 2016 has regulated the principle of confidentiality but has not fully regulated the principle of confidentiality so that efforts are needed. Regulations on mediation experience law unification and reformation of the civil procedural law. The House of Representatives and the government form a special law to regulate mediation to become the legal basis for laws and regulations that use mediation.